2022
DOI: 10.3389/fendo.2022.886451
|View full text |Cite
|
Sign up to set email alerts
|

Add-On Effect of Selenium and Vitamin D Combined Supplementation in Early Control of Graves’ Disease Hyperthyroidism During Methimazole Treatment

Abstract: Prompt and stable control of hyperthyroidism is fundamental to avoid the detrimental effects of thyroid hormone excess, and antithyroid drugs, mainly methimazole (MMI), represent the first-line treatment for Graves’ disease (GD) hyperthyroidism. Decreased serum concentrations of selenium (Se) and calcifediol (25(OH)D, VitD) have been reported in newly diagnosed GD patients in observational studies. Low Se levels might exacerbate oxidative stress by compromising the antioxidant machinery’s response to reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…It showed significant relief of symptoms associated with subclinical hyperthyroidism and improved the quality of life of the patients, but no significant effect was seen in terms of thyroid function (28). In contrast, the results of Gallo, D. showed that MMI + antioxidants (83 ug selenomethionine + 17 ug Se yeast + vitamin D) treatment for 6 months improved thyroid activity more effectively than MMI use that alone (20). We speculate that this difference in results might be related to the type of Se supplementation, dose, duration of treatment and the status of other nutrients in the subject's organism.…”
Section: The Role Of Se In Gdmentioning
confidence: 72%
“…It showed significant relief of symptoms associated with subclinical hyperthyroidism and improved the quality of life of the patients, but no significant effect was seen in terms of thyroid function (28). In contrast, the results of Gallo, D. showed that MMI + antioxidants (83 ug selenomethionine + 17 ug Se yeast + vitamin D) treatment for 6 months improved thyroid activity more effectively than MMI use that alone (20). We speculate that this difference in results might be related to the type of Se supplementation, dose, duration of treatment and the status of other nutrients in the subject's organism.…”
Section: The Role Of Se In Gdmentioning
confidence: 72%
“…This was a randomized, single-blinded, monocentric, controlled, intervention trial (registration number on Eudract Clinical Trial Register SeMMIviD 2017-005050-11) (11). Study protocol, inclusion and exclusion criteria are summarized in Figure 1.…”
Section: Design Setting Treatment and Participantsmentioning
confidence: 99%
“…We recently reported, in a randomized control trial, that in newly diagnosed GD patients the association of cholecalciferol (VitD) and selenium (Se) supplementation with methimazole (MMI), in patients with low VitD and selenium levels, significantly accelerated the control of hyperthyroidism, during the first 6 months of treatment, compared to MMI alone (11). We postulated that this might be, at least partly, due to the influence of micronutrients on the immune response, as suggested by animal and cell system-based studies (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While selenium supplementation was reported to induce no significant therapeutic effect on patients with subclinical hypothyroidism [ 215 ], co-treatment of selenium was found to enhance the efficacy of levothyroxine sodium (LT4) in treating chronic lymphocytic thyroiditis patients with hypothyroidism, yielding greater improvements to inflammatory factors, compared to treatment with LT4 alone [ 216 ]. Selenium supplementation was also found to increase the efficacy of antithyroid drugs in the treatment of Graves’ disease [ 217 ].…”
Section: Signals From Brain To Bodymentioning
confidence: 99%